Developmental toxicity studies on triclopyr acid, triclopyr butoxyethyl ester and triclopyr triethylamine salt in the rabbit. (March 2022) - Barlow, Susan M.; Terry, Claire; Gehen, Sean; Corvaro, Marco
Abstract: Developmental toxicity studies have been conducted in the rabbit on triclopyr acid and its active-ingredient variants, triclopyr triethylamine salt (T-TEA) and triclopyr butoxyethyl ester (T-BEE), which are dissociated or hydrolysed in vivo to triclopyr acid. In this paper, the available developmental toxicity studies on triclopyr acid, T-TEA and T-BEE are summarised and evaluated. For triclopyr acid and T-TEA, there was no evidence of impaired reproductive performance, fetotoxicity, or teratogenicity, even at maternally toxic doses. The no-observed-adverse-effect levels (NOAELs) for developmental toxicity were 75 mg/kg bw per day for triclopyr acid and 100 mg/kg bw per day for T-TEA, equivalent to 72 mg/kg bw per day expressed as triclopyr acid. A study on T-BEE showed increased post-implantation loss and slight increases in skeletal anomalies and variants at the highest dose tested of 100 mg/kg bw per day, a maternally toxic dose. In a follow-up study on T-BEE, focusing on post-implantation loss, no general increase in post-implantation loss was observed, but one animal at 100 mg/kg bw per day with maternal toxicity had complete resorption of implants. The NOAEL for post-implantation loss was 60 mg/kg bw per day, equivalent to 44 mg/kg bw per day expressed as triclopyr acid. It cannot be excluded that T-BEE may be associated with increased post-implantation loss, but it was only seen in association with maternal toxicity. It is concluded that triclopyr acid and its variants are not specifically toxic to the rabbit embryo and fetus, since post-implantation loss only occurred at doses causing maternal toxicity.